Disruption, Ideation and Innovation for Defence and Security - Adlakha-Hutcheon, Gitanjali; Masys, Anthony (Cham : Springer International Publishing : Imprint: Springer, 2022)
This book explores types of disruptions in defence and security, ways to assess disruptions triggered by technological advancements or the lack of legal frameworks; the consequent delays or disruptions to making decisions, creative idea generation and finally the innovative pathways to counter such disruptions. What do disruption, ideation and innovation have in common? How do disruptions, ideas and innovation coexist within defence and security? They all influence and impact decision-making. Disruptions drive decision-making. Ideation raises solutions to resolve the disruptions and innovation brings ideas into life. While disruptions may be common place in the business world, where disruptive technologies displace pre-existing ones; they are less prevalent in defence, even less so within the realm of security. For the last 10 years, there has been talk of disruptive technologies and even adoption of terms such as emerging and disruptive technologies by the largest military alliance-NATO, yet the means to assess these remain elusive. It offers researchers opportunities to assess different types of disruptions, ideate and innovate on scientific grounds to counter disruptions, thereby bolstering the defence and security community's ability to make decisions better. .
1. Understanding the landscape of disruption, ideation and innovation -- 2. System reliability: A Cold War lesson -- 3. Quantum Computing: Unraveling the Hype -- 4. Emerging and disruptive technologies and security: Considering trade-offs between new values and emerging risks -- 5. Human Systems Exploration for Disruption, Ideation and Innovation in Defence and Security Systems -- 6. Total War: A Context for Cybersecurity Innovation -- 7. The impact of the Internet and cyberspace on the Rise in Terrorist Attacks across the US and Europe -- 8. Shocks and Disruptions in Defence and Security: How to lead by Inspiring Innovation and Ideation -- 9. Health security and malaria: a neural network iOS intelligent platform for implementing Seek and Destroy Integrated Vector Management (IVM) policies -- 10. Convergence -- 11. Legal principles governing disruptive technologies in policing: legal innovations? -- 12. Being two steps ahead: the added value of anticipatory intelligence analysis in law enforcement -- 13. Fifth generation Warfare? Violent transnational social movements as security disruptions.
Keywords: Security, International; Politics and war; International Security Studies; Military and Defence Studies